Heamanite-(Ce), (K0.5Ce0.5)TiO3, a new perovskite supergroup mineral found in diamond from Gahcho Kue, Canada - Anzolini, C; Siva-Jothy, WK; LococK, AJ; Nestola, F; Balic-Zunic, T; Alvaro, M; Chinn, IL; Stachel, T; Pearson, DG (American Mineralogist, 2022)
Heamanite-(Ce) (IMA 2020-001), ideally (K0.5Ce0.5)TiO3, is a new perovskite-group mineral found as an inclusion in a diamond from the Gahcho Kue mine in the Northwest Territories, Canada. It occurs as brown, translucent single crystals with an average maximum dimension of similar to 80 mu m, associated with rutile and calcite. The luster is adamantine, and the fracture conchoidal. Heamanite-(Ce) is the K-analog of loparite-(Ce), ideally (NaCe)Ti2O6. The Mohs hardness is estimated to be 51/2 by comparison to loparite-(Ce), and the calculated density is 4.73(1) g/cm(3). Electron microprobe wavelength-dispersive spectrometric analysis (average of 34 points) yielded: CaO 10.70, K2O 7.38, Na2O 0.16, Ce2O3 13.77, La2O3 8.22, Pr2O3 0.84, Nd2O3 1.59, SrO 6.69, BaO 2.96, ThO2 0.36, PbO 0.15, TiO2 45.77, Cr2O3 0.32, Al2O3 0.10, Fe2O3 0.09, Nb2O5 0.87, UO3 0.01, total 99.98 wt%. The empirical formula, based on 3 O atoms, is: [(K0.268Na0.009)(sigma 0.277)(Ce0.143La0.086Pr0.009Nd0.016)(sigma 0.254)(Ca0.326Sr0.110Ba0.033Pb0.001)(sigma 0.470)Th-0.002](sigma 1.003) (Ti0.979Nb0.011Cr0.007Al0.003Fe0.002)(sigma 1.002)O-3. The Goldschmidt tolerance factor for this formula is 1.003. Heamanite-(Ce) is cubic, space group Pm3m, with unit-cell parameter a = 3.9129(9) angstrom, and volume V = 59.91(4) angstrom(3) (Z = 1). The crystal structure was solved using single-crystal X-ray diffraction data and refined to R-1(F) = 2.61%. Heamanite-(Ce) has the aristotypic perovskite structure and adopts the same structure as isolueshite and tausonite. The six strongest diffraction lines are [d(obs) in angstroms (I in percentages) (hkl)]: 2.764 (100) (110), 1.954 (41) (200), 1.596 (36) (211), 1.045 (16) (321), 1.236 (13) (310), and 1.382 (10) (220). The Raman spectrum of heamanite-(Ce) shows two broad bands at 560 and 787 cm(-1), with no bands observed above 1000 cm(-1). Heamanite-(Ce) is named after Larry Heaman, a renowned scientist in the field of radiometric dating applied to diamond-bearing kimberlites, mantle-derived eclogites, and ...